2009
DOI: 10.1111/j.1467-8691.2009.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Cost versus Innovation: Contrasting Outsourcing and Integration Strategies in Manufacturing

Abstract: This paper analyses how two different outsourcing manufacturing strategies relate to plant performance and innovation capability when taking into account the organizational integration of design and manufacturing as well as product complexity. The study discriminates between low-cost-oriented outsourcing and innovation-oriented outsourcing. The empirical data used is based on a survey of 267 engineering firms, of which half have outsourced manufacturing. We found that the two outsourcing strategies do have dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 50 publications
(94 reference statements)
5
31
0
Order By: Relevance
“…For example, Bengtsson et al (2009) found that outsourcing represents a trade-off between improving innovation capability and lowering the cost. The study also showed that manufacturing and supplier integration in product design processes is beneficial when applying innovation-oriented outsourcing, and particularly at complex manufacturing processes.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…For example, Bengtsson et al (2009) found that outsourcing represents a trade-off between improving innovation capability and lowering the cost. The study also showed that manufacturing and supplier integration in product design processes is beneficial when applying innovation-oriented outsourcing, and particularly at complex manufacturing processes.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Schiele et al (2011) found that the procurement of highly innovative products or technology able to achieve the cost saving of the organizations. There exist a trade-off between low cost and innovation strategy (Bengtsson et al, 2009). Sørensen and Torfing (2012) found that innovation assisting much to the corporation in cost saving, product improvement and the most important element is markets extension.…”
mentioning
confidence: 99%
“…Similarly, it may be expected that tactical sourcing lever application represents a trade-off between reducing costs and enhancing innovativeness. Sourcing categories that apply cost-oriented activities may lack focus and mechanisms to use the remaining resources for innovation-oriented activities (Bengtsson et al, 2009;Schiele et al, 2011a). Consequently, the current study proposes the following hypotheses: The following sections present the results of a large-scale survey used to empirically test the hypothesized relationships between tactical sourcing lever application and performance.…”
Section: Performance: Cost Versus Innovationmentioning
confidence: 99%
“…Consequently, the current study proposes the following hypotheses: Furthermore, existing studies have found trade-offs between cost-oriented and innovation-oriented supply management approaches. Dankbaar (2007) and Bengtsson et al (2009) reported that innovation-oriented supply chains lead to inferior cost performance compared with cost-oriented supply chains and vice versa. Similarly, it may be expected that tactical sourcing lever application represents a trade-off between reducing costs and enhancing innovativeness.…”
Section: Performance: Cost Versus Innovationmentioning
confidence: 99%
See 1 more Smart Citation